2022
DOI: 10.1002/adem.202101602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oil‐Soluble Graphene on the Tribological and Rheological Properties of Magnetorheological Fluids

Abstract: Magnetorheological fluid (MRF) is a widely utilized intelligent material that faces the in‐use thickening (IUT) problem caused by wear. As commonly being used polar antiwear agents aggravate the sedimentation of MRF, a new method to improve the tribological properties of MRF using nonpolar oil‐soluble graphene rather than polar additives is proposed. Orthogonal and control experiments conducted with a four‐ball machine show that oil‐soluble graphene greatly improves the antiwear performance of MRF. More specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In addition, Carlson (2002) demonstrated that fluid viscosity increases in the absence of a magnetic field as the number of cycles increases in using MRF in their applications. Also, Numerous studies have made progress on tribological features such as the wear characteristics, tribological performance, and coefficient of friction of MR fluids (Lee et al, 2011; Li et al, 2022; Lv et al, 2022; Sohn et al, 2009; Wong et al, 2001).…”
Section: Particles’ Coatingmentioning
confidence: 99%
“…In addition, Carlson (2002) demonstrated that fluid viscosity increases in the absence of a magnetic field as the number of cycles increases in using MRF in their applications. Also, Numerous studies have made progress on tribological features such as the wear characteristics, tribological performance, and coefficient of friction of MR fluids (Lee et al, 2011; Li et al, 2022; Lv et al, 2022; Sohn et al, 2009; Wong et al, 2001).…”
Section: Particles’ Coatingmentioning
confidence: 99%
“…Li [15] obtained the formula of MRF with excellent frictional properties through experimental research on six different types and different mass fractions of lubricating additives. Lv [16] proposed a new method to improve the tribological properties of MRF using nonpolar oil-soluble graphene, and the results showed that MRF get the best anti-wear effect when graphene concentration in the base oil is 2 mg/ml. Thakur [17] prepared a new kind of MRF with graphite flake, and the results showed that the graphite flake can be used as lubricants to reduce wear.…”
Section: Introductionmentioning
confidence: 99%